Morphological variation suggests that chitinozoans may be fossils of individual microorganisms rather than metazoan eggs. Issue 1908 (14th August 2019) - Liang, Yan; Bernardo, Joseph; Goldman, Daniel; Nõlvak, Jaak; Tang, Peng; Wang, Wenhui; Hints, Olle
Abstract : Chitinozoans are organic-walled microfossils widely recorded in Ordovician to Devonian ( ca 485–359 Mya) marine sediments and extensively used in high-resolution biostratigraphy. Their biological affinity remains unknown, but most commonly, they are interpreted as eggs of marine metazoans. Here, we provide new insights into their palaeobiology from three lines of inquiry. We examine morphological variation of a new, well-preserved Late Ordovician species, Hercochitina violana ; analyse a compiled dataset of measurements on 378 species representing all known chitinozoan genera; and compare these data with the size variation of eggs of both extinct and extant aquatic invertebrates. The results indicate that the magnitude of size variation within chitinozoan species is larger than observed in fossil and modern eggs. Additionally, delicate morphological structures of chitinozoans, such as prosome and complex ornamentation, are inconsistent with the egg hypothesis. Distinct and continuous morphological variation in H . violana is more plausibly interpreted as an ontogenetic series of individual microorganisms, rather than as eggs.